Connecting Clinical Practices with Microbiological and Biochemical Technologies - Rosa María Martínez-Espinosa (Journal of Clinical Microbiology and Biochemical Technology - Peertechz Publications, 2016)
The word technology refers to the knowledge of techniques, skills, methods or processes used to produce goods, services or to reach specific objectives (research, business, etc.). The concept technology can also be used to make reference to devices, computers and factories. The history of technology is as long as human beings' history, however great advances in the field of technology have been developed mainlyduring the last century. In that sense, more than 963000 manuscripts have been published about the design of innovative technologies and their use in almost all fields of knowledge  (http://www.ncbi.nlm.nih.gov/pubmed. Search done using "technology" as key word). It is interesting to highlight that many of the mentioned manuscripts are mainly focused on the optimization of technologies used for analytical/clinical purposes (up to 250000 manuscripts described the use of several technologies in medicine, microbiology, molecular biology and biochemistry) [1]. Thus, medical diagnosis and clinical test has significantly improved thanks to the use of specific microbial, molecular biology and biochemical techniques. As a consequence of this fact, bacterial infections at early stage and early diagnosis of cancer are cheaper and auicker thanks to molecular biology techniques [2,3]. ON the other hand, genetic analysis would be impossible without specific technology optimized at the end of last century for instance [4,5].